(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
In this article, the role of interactive methods in improving the effectiveness of mathematical education, the use of effective methods and tools that are important in the formation of students’ knowledge, skills and competencies in mathematics, and the use of methods aimed at the formation of thinking skills are discussed. A general analysis of theoretically based approaches is described.